Rational design of coumarin fluorophore with solvatochromism, AIE and mechanofluorochromic enhancement properties - Zhang, Kaiming; Shu, Jun; Chu, Wendao; Liu, Xiaoqiang; Xu, Bin; Jiang, Weidong (Dyes and pigments, 2021)
A new fluorophore 7-(diphenylamino)coumarin-4-yl pivalate (DPACP) with solvatochromism, aggregation-induced emission (AIE) and mechanofluorochromic (MFC) enhancement characteristics was rationally designed and synthesized by attaching bulky diphenylamine electron-donor and pivalate ester electron-acceptor to coumarin. With solvent polarity increase from n-hexane to acetonitrile, this molecular displayed a bathochromic shift in the emission wavelength (from 436 nm to 553 nm) and a decrease in the quantum yield (from 81.1% to 2.8%), indicating solvatochromic effect. Also, the AIE behaviors were observed in CH3CN/water and THF/water mixture systems. For example, the PL intensity increased 6 times in mixed solvent (CH3CN: water = 10 : 90) compared to that in pure CH3CN. Moreover, the emission of original powder samples was red-shifted (from 438 nm to 483 nm) with fluorescence enhancement (the solid-state quantum yield increase from 19% to 28%) upon grinding, and the emission behaviors of grinding powder samples could be reverted to original state by wetting with n-hexane. Furthermore, the relationship among the molecular structure, intermolecular interactions and emission properties was investigated by single-crystal diffraction analysis. DPACP had a twisted conformation because of steric hindrance from diphenylamine and pivalate ester groups, which played a decisive role in realizing AIE and MFC enhancement behaviors. The absence of π-π stacking observed in single-crystal structure was the main reason for the AIE property. The MFC enhancement property could be ascribed to the disturbance of weak electrostatic interaction of adjacent molecules upon grinding. The bulky group of pivalate ester was first used to construct MFC molecule, and this work provided insights for developing AIE and MFC materials based on conventional planar fluorophore which was always subject to ACQ effect. [Display omitted] •A new coumarin fluorophore with AIE and MFC enhancement properties was developed.•It was shown that twisted molecule conformation was crucial for AIE and MFC behaviors.•The bulky group of pivalate ester was first used to construct AIE and MFC molecule.•The fluorescence quantum yields of the compound in n-hexane reached to 0.81.